A New Type of Physical Activity from an Ancient Tradition: The Sardinian Folk Dance "Ballu Sardu". Issue 3 (September 2015) - Cugusi, Lucia; Massidda, Myosotis; Matta, Daniela; Garau, Emanuele; Di Cesare, Rosina; Deidda, Martino; Satta, Gianmario; Chiappori, Paolo; Solla, Paolo; Mercuro, Giuseppe
The aim of our study was to determine if the Sardinian folk dance ballu sardu (BS) can be identified as an effective workout regimen in terms of its exercise intensity (EI) and energy expenditure (EE) and if people who perform BS fulfill the recommendations of the American College of Sports Medicine on the prescription of exercise in healthy subjects. Twenty healthy volunteers (10 men, 10 women, 35.2 ± 6.3 years of age, BMI 23.0 ± 3.4 kg/m 2 ) with BS experience (mean = 20.7 ± 8.9 years) were enrolled. All subjects underwent a maximal cardiopulmonary exercise test. Then they carried out a performance of about a quarter of an hour of BS in its most common variant of dance in a circle, ballu tundu. During the BS performance, the dancers wore a heart rate monitor to record all relevant data. The dancers displayed a good aerobic capacity (VO2 max 44.1 ± 3.2 ml·kg -1 ·min -1 ). Their average HR during the BS execution was 146.3 ± 5.3 bpm, corresponding to an EI of 79.9% ± 6.5% of HRmax. The estimated average VO2 was 78.6% ± 15.4% of VO2 max; MET/min and EE were 9.8 ± 1.5 and 11.2 ± 2.4 Kcal/min, respectively. It is concluded that the BS can be described as a vigorous physical activity. An ancient yet still widespread leisure activity embedded in the Sardinian culture, it meets some contemporary exercise recommendations for a healthy lifestyle.